Kenya Commercial Banks are Star Performers –Myth or Truth? Exploratory Empirical Evidence from Nairobi Securities Exchange (NSE) - Muinde, Patrick Mumo; Karanja, James Mwangi (International Journal of Economics and Financial Issues, 2017)
The profitability of commercial banks in Kenya has been a subject of intense policy debate over the past two decades. This paper explores and adduces evidence that the perceived abnormal profitability in the industry is reflected in stock returns. The study utilizes time series data obtained from the NSE and five macroeconomic variables for the period 1996: 2015. We regress portfolio monthly excess returns, predict and graph these returns to determine if the banking sector outperforms other sectors of the economy. The empirical evidence presented here suggests that the banking industry outperforms other sectors of the economy in Kenya. Keywords: Commercial Banks; Portfolio Returns JEL Classifications: A23, C22, E44